2016
DOI: 10.1088/0951-7715/29/2/375
|View full text |Cite
|
Sign up to set email alerts
|

Toward pruning theory of the Stokes geometry for the quantum Hénon map

Abstract: The Stokes geometry for the propagator of the quantum Hénon map is studied in the light of recent developments of the exact WKB analysis. As the simplest possible situation the Hénon map satisfying the so-called horseshoe condition is closely analyzed, together with listing up local bifurcation patterns of the Stokes geometry. This is exactly in the same spirit as pruning theory for the classical horseshoe system, and the present paper is placed as the first step to establish pruning theory of the Stokes geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…However, a naive treatment of the Stokes phenomenon was shown to break down. In particular, we demonstrated that there is a situation where even exponentially decaying contributions should be dropped, which is one piece of evidence suggesting that the Stokes phenomenon for the normal form Hamiltonian systems must be highly non-trivial [36].…”
Section: Summary and Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…However, a naive treatment of the Stokes phenomenon was shown to break down. In particular, we demonstrated that there is a situation where even exponentially decaying contributions should be dropped, which is one piece of evidence suggesting that the Stokes phenomenon for the normal form Hamiltonian systems must be highly non-trivial [36].…”
Section: Summary and Discussionmentioning
confidence: 72%
“…As seen in the phase space portrait drawn in figure 11, the system has two symmetric wells located at the positions q = ±1 respectively, and nonlinear resonance like equi-energy contours appear around each well. Figure 11: Equi-energy contours for the Hamiltonian (36).…”
Section: Normal Form Hamiltonianmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant progress has been made towards eliminating such divergences in discrete time systems based on Adachi's work on the Principle of Exponential Dominance (PED). 4,[8][9][10] However the PED requires comparison of trajectory pairs which can only be found numerically via a root search in the complex trajectory manifold. In continuous time dynamics, such a root search is quite challenging and has been successful so far only for relatively short times.…”
Section: Introductionmentioning
confidence: 99%